A systems study of nutrient uptake in plants - Ajmera, Ishan (2016)
The case for improving Phosphorus-Use Efficiency in crops is widely recognised. Although much is known about the underlying molecular and regulatory mechanisms, improvements have been hampered by the extreme complexity of phosphorus (P) dynamics in soil and plants (across all physical scales), including its soil chemistry and uptake, distribution and deficiency responses in plants. The urgency and direction of phosphate research is also being driven by the availability of finite P stocks to farmers and reducing environmental hazards. Thus, systems approaches become essential to identify the most potent (combinations of) target genes for improving phosphate uptake and utilisation in crops. This study has applied these approaches with the aim of increasing understanding of the regulation of phosphate uptake at three separate spatial scales, primarily in rice, but also in Arabidopsis.